Business planning : the key to success - Coulthard, Max.; Coulthard, Max.; Howell, Andrea (South Melbourne : Macmillan Education Australia, 1996)
This book is about: Direction; Organizational functions; Systems; Growth and contingencies; Putting it all together; Feasibility;...
Keywords: Business; Management; Strategic planning; Business planning